Proposta e aplicação de uma sistemática baseada na gestão do conhecimento para a melhoria do processo de compras públicas - Kariyado, Monica Yukie (2016)
The purchasing management plays a strategic role in public organizations, since their function is supply them with inputs, raw materials and services needed to achieve their goals. However, the public procurement processes are highly regulated and bureaucratic, causing disorders affecting the performance of acquisitions. The objective of this research was to propose and implement a system for improving the internal purchasing process in a Federal Institution of Higher Education (IFES) based on Knowledge Management. The research method used was action research and the organization studied was the Federal University of São Carlos (UFSCar). The results comprised the development of a systematic, based on knowledge management, to improve the purchasing process and its application in unit case, which involved four steps: 1] diagnosis of the problem situation: mapping process information flow purchasing, identification of stakeholders, problem causes, the knowledge conversion processes; identification of potential knowledge management initiatives and the selection of operational focus; 2] implementation; 3] Evaluation and 4] solution Replication. The conclusion is based on theoretical discussion and analysis of results that knowledge management can contribute to the improvement of public organizations purchasing process by implementing solutions focused on the actors and the knowledge conversion processes.